2020
DOI: 10.1101/2020.04.21.053405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ligand-directed covalent labelling of a GPCR with a fluorescent tag

Abstract: Here, we describe rational design of a compound that covalently and selectively labels a G protein-coupled receptor (GPCR) in living cells with a fluorescent moiety. Using wild-type adenosine A2A receptor as a model system, we show fluorescent labelling without impeding access to the orthosteric binding site and demonstrate its use in endogenously expressing systems. This offers a non-invasive and selective approach to study function and localisation of native GPCRs.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…[20] For many other protein modification approaches, an additional element is used to achieve a higher level of site selectivity. This element, which is often a known ligand or inhibitor for the protein of interest, [21][22][23][24] displays affinity for the protein and directs the reactive moiety -whether reactive by itself or activated by a catalyst-to a specific site on the protein. Of the ligands that have been applied, those that are based on biological entities have shown tremendous promise.…”
mentioning
confidence: 99%
“…[20] For many other protein modification approaches, an additional element is used to achieve a higher level of site selectivity. This element, which is often a known ligand or inhibitor for the protein of interest, [21][22][23][24] displays affinity for the protein and directs the reactive moiety -whether reactive by itself or activated by a catalyst-to a specific site on the protein. Of the ligands that have been applied, those that are based on biological entities have shown tremendous promise.…”
mentioning
confidence: 99%
“…The use of UV-Vis spectroscopy can inform on the type of modified residue, however, its use is limited to reactions wherein covalent transfer leads to changes in spectral properties. The TR-FRET experiments as applied previously 75 do not give realtime insight into the rate of covalent labeling nor suggest the amino acid residue being modified.…”
Section: Tr-fret Based Assay To Assess Covalent Nbd Transfer To Cb2rmentioning
confidence: 95%
“…In previous work on ligand directed chemistry, covalent labeling was validated by Western blotting, 53 mass spectrometry, 44,73,74 UV-Vis spectroscopy 63 or time-resolved Förster resonance energy transfer (TR-FRET). 75 All of these approaches suffer from disadvantages.…”
Section: Tr-fret Based Assay To Assess Covalent Nbd Transfer To Cb2rmentioning
confidence: 99%
“…Western blotting with an anti-biotin antibody showed that copper(II) is necessary for N-terminal modification, which is consistent with the peptide study (Figure 5C, lanes 3 and 4). The tryptic digestion of biotinmyoglobin revealed that the aldol reaction exclusively occurred on the N-terminus-containing fragment [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] (Figure S58 and S59). The modification reaction of myoglobin with 23 reached a 77 % yield after 3 h (Figure S60).…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…Bioconjugation reactions for the chemical modification of proteins have been rapidly developed to meet the growing demand for applications in activity-based protein profiling, [1,2] studies on cellular processes, [3][4][5] the construction of protein chimeras [6,7] and biopolymer-based materials, [8,9] and the development of biopharmaceuticals. [10][11][12] These reactions enable the effortless attachment of synthetic molecules and/or biopolymers to proteins, thereby allowing the creation of new functionalized proteins that do not naturally exist.…”
Section: Introductionmentioning
confidence: 99%